The Relationship Between Love Style and Emotional Divorce With the Mediating Role of Resilience and Social Support in Couples With Experience of Emotional Divorce - Shahi, Fariba; Eskandari, Hossein (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The aim of this study was to examine the relationship between love style and emotional divorce with the mediating role of resilience and social support in couples who have experienced emotional divorce. Methods and Materials: The statistical population of this correlational-descriptive study included all couples with emotional divorce experience who referred to counseling and psychological service centers in District 5 of Tehran in 2023. For this purpose, 300 individuals were selected through purposive voluntary sampling as the statistical sample. The research method was descriptive and correlational in nature, utilizing a path analysis design. To measure the research variables, the following instruments were used: Sternberg’s Triangular Love Scale (1986), the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988), the Emotional Divorce Scale (Gottman, 1994), and the Connor-Davidson Resilience Scale (CD-RISC) (Connor & Davidson, 2003). The collected data were analyzed using the Sobel test and processed with SPSS and AMOS software. Findings: The research findings indicated that love style, resilience, and social support were significantly and negatively correlated with emotional divorce (p < .01). Moreover, resilience and social support served as mediating variables in the relationship between love style and emotional divorce in couples (p < .01). Conclusion: Based on these findings, it can be concluded that love style, resilience, and social support play a significant role in couples’ emotional divorce.